AnaIisis Muatan NiIai-nilai Karakter Pada Buku Siswa Tema Indahnya Kebersamaan Kelas IV Sekolah Dasar - Momela Waskita Negara; Sri Ken Kustianti; Dalifa Dalifa (JURIDIKDAS, 2020)
This study aims to analyze the character values in student books on the theme of the beauty of togetherness, the sub-theme of togetherness in the diversity of grade IV elementary schools. This type of research is qualitative research. The method used is descriptive analysis method. The data in this study were books of fourth grade elementary school students. Collecting data in this study using literature study. The analysis technique used is content analysis (content analysis). The results of the study were (1) The analysis process was initiated by reading students' books on the beauty of togetherness, the sub-theme of togetherness in the diversity of grade IV elementary schools. Extension of participation or frequency of reading, conducting observations, carefully and in detail on an ongoing basis, checking the validity of the data, (2) the results of the analysis of the student book on the theme of the beauty of togetherness, the sub-theme of togetherness in the diversity of grade IV primary schools obtained six character values, namely: religious, honest , discipline, responsibility, caring and self-confidence. The conclusion of this research is that from the students' book analyzed, there are six character values, namely: religious, honest, disciplined, responsibility, caring and self-confidence. These values appear or appear explicitly and implicitly in every quote in the story. Then the analysis results are in accordance with the indicator character values. Keywords: Student book,  character value